(untitled) (Proceedings of International Educators Conference, 2023)
This article presents comparative results of tests of fire-rescue and other equipment by existing methods and on a new machine developed at the Academy of the Ministry of Emergency Situations of the Republic of Uzbekistan with a view to their further implementation into practice.